2019
DOI: 10.14434/josotl.v19i1.26777
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Collaborative, Project-based Learning Models in Introductory Science Courses

Abstract: Collaborative, project-based learning models have been shown to benefit student learning and engagement in the STEM disciplines. This case study evaluates the use of highly collaborative project- and problem-based learning models in introductory courses in the geosciences and biology. In the geosciences, we developed project-based modules with a strong local focus. Student teams worked on three project-based laboratories dealing with the local geology/geomorphology, water quality of a local stream, and local f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 23 publications
2
12
1
2
Order By: Relevance
“…Thus, the findings of this study can help us better understand the positive effects of prior course redesign efforts (Hearne & Henkin, 2011;Vaughan, 2010;Wilson et al, 2018) by associating them with improvements in students' self-efficacy (Fini et al, 2018). It can also be argued that the evidence presented in this study supports the claim that students' perceptions of their increased academic abilities are not unwarranted and can be affirmed by their academic performance in the future (Cȩlik et al, 2018;Das et al, 2019;Huysken et al, 2019;Olson, 2017). This knowledge can serve as an important implication for all FYS faculty and staff working with students who are struggling academically, enroll in colleges under-prepared, or find it particularly hard to overcome academic barriers and roadblocks.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Thus, the findings of this study can help us better understand the positive effects of prior course redesign efforts (Hearne & Henkin, 2011;Vaughan, 2010;Wilson et al, 2018) by associating them with improvements in students' self-efficacy (Fini et al, 2018). It can also be argued that the evidence presented in this study supports the claim that students' perceptions of their increased academic abilities are not unwarranted and can be affirmed by their academic performance in the future (Cȩlik et al, 2018;Das et al, 2019;Huysken et al, 2019;Olson, 2017). This knowledge can serve as an important implication for all FYS faculty and staff working with students who are struggling academically, enroll in colleges under-prepared, or find it particularly hard to overcome academic barriers and roadblocks.…”
Section: Discussionsupporting
confidence: 55%
“…The available studies, however, agree that PjBL can be used as a powerful tool to improve student learning. The most pronounced positive effects have been recorded in the domain of academic performance (Cȩlik et al, 2018;Huysken et al, 2019) and motivation (Amaral et al, 2018;Requies et al, 2018). Additional results have been documented for improving students' conceptual understanding (Coruhly & Nas, 2018), advancing research skills (Saliba et al, 2017), and enhancing participants' self-efficacy, teamwork, and communication skills (Fini et al, 2018).…”
Section: Project-based Learningmentioning
confidence: 98%
“…Studies on content area classes at the university level report several benefits for the use of PBL, such as the development of cross-curricular competencies including autonomy, teamwork, problem solving and critical thinking (Pacheco et al, 2018), as well as student interaction and collaboration (El-Maaddawy et al, 2018;Gao & Avis, 2019;Huysken et al, 2018;Rooij, 2009). In the neighbouring Qatari higher education context, Khandakar et al (2020) report on a case study where they employed a multi-course project-based learning (MPL) approach in two electrical engineering interdisciplinary undergraduate courses at Qatar University and investigated its impact on Education for Sustainable Development.…”
Section: Studies Examining Pbl In Learning/teaching In Higher Educationmentioning
confidence: 99%
“…in the last few decades there has been a shift to more open-ended approaches to teaching that value inquiry, reflection, problem-based learning, discussion and collaboration, and self-directed learning (Harmer & Stokes, 2018;Holm, 2011;Bell, 2010). The literature on student learning revealed that learning by doing and experiencing is much more meaningful and permanent for the students than passive learning (Bell, 2010;Holst, 2003;Howard, 2002), and that this is one of the main constituents of contemporary education.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation